PENGARUH FASILITAS TERHADAP KEPUASAN PELANGGAN DI ASTON MADIUN HOTEL & CONFERENCE CENTER - Ninik Srijani; Achmad Sukma Hidayat (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2018)
This study aims to determine the facility in Aston Madiun Hotel & Conference Center. To determine customer satisfaction at Aston Madiun Hotel & Conference Center. To know the facility is there any influence on customer satisfaction Aston Madiun Hotel & Conference Center. The method in this research is descriptive quantitative method, while the sampling technique in this research is cluster sampling, that customers who stayed at Aston Madiun Hotel & Conference Center with a number of 101 respondents. Collecting data using questionnaires and observation methods. In analyzing the data the instruments used are validity and reliability. To test the assumption using normality test. And to test the hypothesis of this study using simple linear regression analysis of the data, the determinant coefficient, and t test. The results were obtained a total score of facilities has a value above the average of 59 respondents, while below the average of 42 respondents. Y = 11.727 + 0,820X. The constant equal to 11.727, meaning that if the variable or constant fixed-value amenities, the amount Customer Satisfaction is 11.727. This means that without the influence of the amenities variable customer satisfaction will continue to have a value of 11.727. A regression coefficient of 0.820 has the sense that if an increase in 31 the Facility variables Customer satisfaction will rise by 0.820 of one unit assuming other variables remain. The coefficient is positive means that there is a positive relationship Facility and Customer Satisfaction. Based on the analysis above can be seen the value of R2 is 0.799. So the influence of facilities to customer satisfaction Aston Madiun Hotel & Conference Center 79.9% while the remaining 20.1% is influenced by other factors. So it can be concluded that the facility has an influence on customer satisfaction. T test calculations obtained was 19.810 while ttabel 1.937. Thus H0 is rejected, meaning that there is influence overall facility to customer satisfaction.